Dengue Fever in Pregnancy - Maternal and Fetal Outcome (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background and objectives: There has been a lot of concern related to dengue infection in pregnant women in recent years due to an increase in number of dengue infections worldwide. Dengue fever during pregnancy is associated with early pregnancy failure, preterm delivery, low birth weight babies, prematurity, and occasionally neonatal mortalities. The primary objective is to find out the maternal and fetal outcome of pregnancy affected by Dengue fever.Materials and Method: This is a prospective observational study, conducted over a period of 3 months from 1st July to 30th September 2023 in Dhaka Medical College Hospital, Dhaka, Bangladesh.Result: Out of the 44 pregnant patients admitted with suspected dengue infection, 56.8% were diagnosed serologically positive by NS1 and 43.2% by Dengue IgM . Fever was found in 100% patients and Thrombocytopenia was found in 45.9% patients, PPH in 13.6%. Regarding obstetric management 25% got conservative management ,27.2% delivered vaginally and 38.6% undergone LSCS. About 25% pt needed to shift ICU in antenatal and postnatal period.4.5% were maternal mortality in this study period. On the other hand 13.7% were still born and 13.7% of the babies required NICU admission due to prematurity and low birth weight.Conclusion: Dengue related complications are high in pregnancy. Timely and precise interventions in dengue infected pregnant women are needed for optimal outcome. Early detection and access to proper medical care in this specific group by multidisciplinary team can reduce complications and mortality.J Bangladesh Coll Phys Surg 2023; 41: 21-24